PENERAPAN PSAK 10 ATAS SELISIH KURS DAN TRANSAKSI MATA UANG ASING PADA LAPORAN KEUANGAN PT SUPER ENERGY TBK - Susilawati; Wahyuni, Nanik (I-Economics, 2024)
PT Super Energy is an international company operating in the oil and gas sector which experienced losses in its financial reports for 3 consecutive years, namely in 2020 - 2022. Based on these losses, researchers focused on investigating whether there was a relationship between these losses. year and implementation of PSAK 10 and foreign currency transactions and identifying their fairness. In previous research, the majority only used one financial reporting period, while this research will use three financial reporting periods, namely 2020 - 2022. The research method used is qualitative research with a case study method approach and documentation with value objects from exchange rate differences and transactions. foreign currency from the financial statements of PT Super Energy Tbk. The results of this research indicate that the presentation of exchange rate differences in PT Super Energy's financial statements does not show the same results as PSAK 10, however, because the value resulting from exchange rate differences is not material, it does not affect the presentation of PT Super Energy's financial reports.